Animal cloning : the science of nuclear transfer - Panno, Joseph (New York : Facts On File, 2005)
Discusses the history of cloning experiments, the creation of Dolly the sheep, transgenic clones, organ farming, and ethical and legal issues, and presents overviews of related topics, including eukaryote cells, recombinant DNA, gene therapy, the Human Genome Project, the Belmont Report, the Gelsinger investigation, and clinical trials.
Includes bibliographical references and index.
Wilson's Senior High School.
Wilson's Senior High School, November 2006.
Young Adult
Keywords: Cell nuclei -- Transplantation -- Popular works; Cloning -- Popular works; Cells; Cloning